[Teaching, Learning and Researching Experiences] - Kidney, James (1999)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Managerial resistance to change: Romania’s quest for a market economy - Catana, D.; Catana, A.; Finlay, J.L. (Journal of East European Management Studies, 1999)
This exploratory investigation relates traditional theories on resistance to change to privatization of the Romanian economy. The authors identified several “inhibitors” which have served to stall Romania’s attempts to achieve a free-market economy. While a lack of practical training in western-style management practices may be a limiting factor, Romanian managers are generally open to change. However, they are still deeply rooted in the thought processes instilled during Romania’s command economy and a belief that the size and economic importance of their firms will serve as buffers against the “agents of change”. To the extent that change is viewed as a threat to their personal interests, resistance can be expected. The question, “what is in it for me?”, must be satisfactorily addressed if Romanian managers are expected to become active partners in implementing necessary changes. © 1999, Nomos Verlagsgesellschaft mbH und Co. All rights reserved.
Keywords: dept.mgt